2020
DOI: 10.1111/napa.12137
|View full text |Cite
|
Sign up to set email alerts
|

Unique Issues for Resettling Refugees from the Congo Wars

Abstract: In recent years, many anthropologists in the United States have become involved with organizations that serve newly resettled refugees, especially as budgets for the agencies have been severely cut since 2017. Here, we reflect on some of our experiences working with Refugees from the Congo Wars (RFCWs) and address some of the challenges we have faced as applied/practicing anthropologists and resettlement support personnel. Juxtaposing a larger southern city—Tampa—with a smaller rustbelt city—Akron—we see many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…McElrone et al [ 30 ] elaborate that many Congolese and Burundian refugees desire to continue consuming their traditional foods and will go to great lengths to access them. One of the few studies in Ohio also found that Congolese cherish their traditional foods [ 11 ]. From an integration Acculturation Theory perspective, and also recommended by McElrone et al [ 30 ], we suggest organizations provide Congolese refugees with orientation services to local grocery stores that would offer them opportunities to find local food similar to their traditional foods.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…McElrone et al [ 30 ] elaborate that many Congolese and Burundian refugees desire to continue consuming their traditional foods and will go to great lengths to access them. One of the few studies in Ohio also found that Congolese cherish their traditional foods [ 11 ]. From an integration Acculturation Theory perspective, and also recommended by McElrone et al [ 30 ], we suggest organizations provide Congolese refugees with orientation services to local grocery stores that would offer them opportunities to find local food similar to their traditional foods.…”
Section: Discussionmentioning
confidence: 99%
“…Findings also suggest that refugees in neighborhoods with a higher percentage of Black residents reported less satisfaction overall. An additional study by Mahoney et al [ 11 ] examined the challenges of Congolese refugees in Akron, Ohio, and Tampa, Florida. They revealed when working with refugees from the Congo Wars and focused on the timing of arrival in the United States, community and class, schooling, gender and family, and food and diet.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations